TINGKAT SUKU BUNGA PINJAMAN DAN KINERJA KEUANGAN PERBANKAN: STUDI KASUS PADA BPR PT PRISMADANA - Sarah Usman (Jurnal Riset Manajemen dan Bisnis, 2011)
The purpose of this study is to analyze the role of loan interest and its implication towardsRural Bank’s financial performance. Database collected from primer data is based onobservation, meanwhile secondary data from Rural Bank’s financial statements during2006-2008 period. This study based on net interest margin analysis. The role of loan interestand it’s implication proxied by net interest income indicator.This study shows that anincrease in interest income (Net Interest Income) at Rural Bank due to an increase of it’slending activities for five years. Thus, loan interest income has important role on theincreasing perfomance of PTPrismadana rural bank's finance.Keywords: Interest Rate, Financial Performing, BPR